Bearing capacity of shallow circular and strip foundation resting on two layered clays - Kumar P.; Chakraborty M. (My University, 2025)
By using the lower and upper bound limit analysis in conjunction with finite elements and nonlinear optimization undrained bearing capacity of rough circular and strip foundation resting on two layered clayey soil is computed. The circular and the strip foundation are analyzed by assuming the axisymmetric and the plane strain condition, respectively. The clay is assumed to follow Mohr–Coulomb yield criteria and an associated flow rule. Results are provided for different (i) t/b ratio and (ii) cu1/cu2 ratio; where, t = top layer thickness, b = diameter/width of the foundation, and cu1 and cu2 refers to the undrained cohesion of the top and bottom layers, respectively. The results indicate that there is an optimum t/b ratio beyond which the bearing capacity remains the same. The magnitude of the optimum t/b ratio depends on cu1/cu2 ratio and the type of the foundation. For the same cu1/cu2 ratio, the optimum t/b ratio for the circular foundation is less in comparison to the strip foundation. The obtained numerical solutions are in good agreement with the previously available literatures. Failure patterns and nodal velocity contour are provided for a few cases. © Springer Nature Singapore Pte Ltd. 2020.